(untitled) (Research, Society and Development, 2024)
Histoplasma capsulatum is a dimorphic fungus present in soil and the causative agent of histoplasmosis in humans and animals, including cats. This disease is of great importance due to its potential to cause serious and disseminated infection. It has a high prevalence in the Americas, with human outbreaks reported in Brazil since the 1940s, most related to cave exploration. In cats, the nasal cavity is the most affected area, and the presence of clinical signs associated with upper respiratory tract infection, such as sneezing, dyspnea and coughing, is common. The fungus can spread through contiguity to underlying tissues or through the hematogenous route to any organ, including the skin. This work aimed to report the clinical case of a cat treated in Rio de Janeiro with edema in the right forelimb and persistent lameness for five months. A radiographic examination of the affected limb was performed. Three bone fragments were obtained by biopsy for bacterial and fungal culture, in addition to histopathological evaluation. Radiological examination of the affected limb showed a cystic structure in the distal ulnar epiphysis (bone cyst). There was no bacterial growth in the bacteriological culture. Histoplasma capsulatum was isolated in culture and histopathological examination revealed an intense inflammatory infiltrate composed of neutrophils and macrophages compatible with a pyogranulomatous process. Therefore, this is the first report of feline histoplasmosis with bone cyst manifestation.